pH-triggered CS@ZnO2 nanocomposites: Self-activated ROS generation for efficient bacterial eradication - Zhang, Yu; Liu, Jun; Li, Sha; Zhou, Jinhua; Liu, Jiushan; Huang, Yan (Frontiers in Bioengineering and Biotechnology, 2025)
Functional nanomaterials based on reactive oxygen species (ROS) have attracted considerable attention in the treatment of bacterial infections, owing to their high sterilization efficiency and low tendency to induce drug resistance. Natural polymers, known for their excellent biocompatibility, have been widely used in the development of antibacterial dressings. In this study, chitosan-zinc peroxide composite dressing (CS@ZnO2) was synthesized using zinc acetate and chitosan as primary raw materials, and comprehensive characterizations were performed. Under the slightly acidic conditions of bacterial infections, CS@ZnO2 could self-decompose to release H2O2 and produce large amount of ROS, which would cause damage to bacteria. The in vitro antibacterial properties of CS@ZnO2 were investigated using Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) as representative pathogens. The results demonstrated that CS@ZnO2 exhibited potent antibacterial efficacy against both S. aureus and E. coli. This research provides an important theoretical foundation and technical support for the development of novel antibacterial materials, and has the potential to improve the efficacy of treatments for bacterial infections in the future.